2010
DOI: 10.1016/j.neuron.2010.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Calcium Controls Background Current and Neuronal Excitability via an UNC79-UNC80-NALCN Cation Channel Complex

Abstract: SUMMARY In contrast to its extensively studied intracellular roles, the molecular mechanisms by which extracellular Ca2+ regulates the basal excitability of neurons are unclear. One mechanism is believed to be through Ca2+'s interaction with the negative charges on the cell membrane (the charge screening effect). Here we show that, in cultured hippocampal neurons, lowering [Ca2+]e activates a NALCN channel-dependent Na+-leak current (IL-Na). The coupling between [Ca2+]e and NALCN requires a Ca2+-sensing G prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
280
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(295 citation statements)
references
References 62 publications
(111 reference statements)
11
280
3
1
Order By: Relevance
“…The characteristic behavior of mature [14][15][16][17]] neuronal cultures in standard physiological medium (1-1.5 mM…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic behavior of mature [14][15][16][17]] neuronal cultures in standard physiological medium (1-1.5 mM…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, calcium is important for determining the single cell excitability, for example, by regulating leak currents into the neuron via the NALCN (sodium leak channel) (14,15).…”
mentioning
confidence: 99%
“…Two ion channels have been identified that might contribute to such responses. NALCN, a Na + leak channel (33) with minimal Ca 2+ permeability, is activated in hippocampal pyramidal cells indirectly by low [Ca 2+ ] o by a G-protein-coupled receptor (11). TRPM7 can also be activated in hippocampal neurons under conditions in which divalent cation concentrations fall, although normal intracellular Mg 2+ levels are expected to minimize such activation (34).…”
Section: Discussionmentioning
confidence: 99%
“…The bath solution contained 150 mM Na + , 5.4 mM K + , 1 mM Mg 2+ , 150 mM Cl − , 20 mM glucose, 10 mM Hepes, and 1.5 mM Ca 2+ (unless otherwise indicated), pH 7.4 adjusted by methanesulfonate, ∼330 mOsm. These solutions are similar to those used in other current-clamp studies (11,36). Data acquisition was as described above for N2A cell whole-cell voltageclamp experiments.…”
Section: Methodsmentioning
confidence: 99%
“…These results collectively suggest that ATP13A4 likely plays a key role in behavioral evolution during chicken domestication. Similarly, the gene UNC80, which has a function in the nervous system [23,24], also experienced positive selection and had the highest identified XP-EHH score by the sliding window analysis ( Figure 1B).…”
Section: Positively Selected Genes In Domestic Chickens Compared Withmentioning
confidence: 94%